Penerapan Algoritma K-Means Untuk Klasterisasi Akseptor Keluarga Berencana Modern di Sumatera Barat - Wicaksono, Putut; Defit, Sarjon; Nurcahyo, Gunadi Widi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The Regulation of the National Population and Family Planning Agency number 11 of 2020 concerning modern contraceptive methods including the Female Operation Method (MOW)/female sterilization, Male Operation Method (MOP)/male sterilization, IUD/spiral/Intrauterine Contraceptive Device (IUD), implant/implant, injection, pill, and condom. This study aims to apply and test the K-Means algorithm by measuring the level of accuracy in clustering Districts/Cities based on the use of modern contraceptives. The method used in this study is the K-Means Clustering algorithm to produce 3 clusters, namely district/city clusters with high, medium, and low acceptor usage. The stages of the K-Means Clustering algorithm are as follows: Determining the number of clusters, Determining the initial centroid point randomly, Calculating the closest distance between data and centroid, Grouping data into each cluster, If the cluster changes, the process continues to the next iteration, if there is no change, the iteration process is stopped. The data set processed in this study came from the BKKBN of West Sumatra Province. This study used a data set of 383,609 from 19 districts/cities based on the use of modern contraceptives. The results of this study indicate that the performance of the K-Means method in cluster analysis produces 3 clusters consisting of low modern contraceptive users of 5 districts/cities in cluster 0 or 26.32%, moderate modern contraceptive users of 7 districts/cities in cluster 1 or 36.84%. users of modern contraceptives are high as many as 7 districts/cities in cluster 2 or 36.84%. Therefore, this study can be a reference for district/city governments in intervening in population control and family planning programs.